MLTI-18. PRECISION IMAGING OF METASTATIC AND PRIMARY BRAIN TUMORS AFTER RADIATION WITH 18F-FDOPA PET-MRI IS FEASIBLE AND COST EFFECT. (12th August 2019) - Aboian, Mariam; Ravanfar, Vahid; Bahroos, Emma; Tong, Elizabeth; Taylor, Jennie; Oberheim Bush, Nancy Ann; Seo, Youngho; Cha, Soonmee; Pampaloni, Miguel Hernandez
Abstract: PURPOSE: Post-radiation changes in the brain can mimic tumor recurrence on MRI, requiring multiple short term follow-ups to differentiate tumor progression from radiation necrosis. We propose combining functional and anatomic imaging with FDOPA PET tracer in hybrid PET-MRI to improve detection of tumor recurrence. MATERIALS AND METHODS: Seventeen adult patients treated with radiation therapy were identified - four with metastatic disease from breast and lung cancer and thirteen with primary brain glioma (11 IDH wildtype glioblastoma and 2 astrocytoma). Patients were scanned on hybrid PET-MRI (GE Healthcare) with clinical MRI brain sequences and dynamic FDOPA uptake. Dynamic FDOPA uptake within these tumors over 45 minutes after tracer injection was analyzed and compared to ADC histogram analysis. RESULTS: For each of the patients, clinical multi sequence gadolinium enhanced MRI and dynamic PET imaging for up to 45 minutes with 18 F-FDOPA amino acid tracer was obtained. The total cost savings of scanning 17 patients in groups was 51.4% ($28, 321), as opposed to the cost of individual radiosynthesis performed for each study. Quantitative analysis of tracer uptake in striatum, internal carotid artery, and superior sagittal sinus were performed with appropriate accumulation and subsequent washout of tracer respectively. Successful dynamic FDOPA uptake within the tumor was seen in all patients and ratio of tumor to contralateral ROI were found to range from 1.8–4.5. While raw SUV values did not differentiate between recurrent tumor and radiation changes, T/C SUVmax ratios were elevated to 4.5 in recurrent glioblastoma, 2.5 in hypoxic treated glioblastoma, and 1.8 in non-recurrent metastatic breast cancer after gamma knife treatment. CONCLUSION: Batch imaging of patients with [ 18 F]FDOPA PET-MRI is feasible and cost effective. Understanding radionuclide synthesis process is critical for increasing accessibility of novel PET tracers to patients and results in significant cost savings.